Potential Roles for Ubiquitin and the Proteasome during Ribosome Biogenesis - Stavreva, Diana A. (American Society for Microbiology, 2006)
We have investigated the possible involvement of the ubiquitin-proteasome system (UPS) in ribosome biogenesis. We find by immunofluorescence that ubiquitin is present within nucleoli and also demonstrate by immunoprecipitation that complexes associated with pre-rRNA processing factors are ubiquitinated. Using short proteasome inhibition treatments, we show by fluorescence microscopy that nucleolar morphology is disrupted for some but not all factors involved in ribosome biogenesis. Interference with proteasome degradation also induces the accumulation of 90S preribosomes, alters the dynamic properties of a number of processing factors, slows the release of mature rRNA from the nucleolus, and leads to the depletion of 18S and 28S rRNAs. Together, these results suggest that the UPS is probably involved at many steps during ribosome biogenesis, including the maturation of the 90S preribosome.